Effect of Er, Cr: YSGG laser irradiation in the physics properties of different dentin bonding systems (Research, Society and Development, 2022)
The aim of this study was to evaluate the effect of Er, Cr: YSGG laser irradiation in the physics properties of the different dentin bonding systems (DBS) applied in dentin substrate.This study presented two variation factors: laser, divided into two levels (Er, Cr: YSGG [L] and Control - not irradiated [C]) and DBS divided into four levels (AdperTM Scotchbond Multipurpose [MP], AdperTM Single Bond 2 [SB], ClearfilTM SE Bond [CSE], ScotchbondTM Universal Adhesive [SU]). The response variables were water sorption/solubility (mg/mm3) [WS/WSB], degree of conversion (%) [DC], microtensile bond strength (MPa) [MS] and scanning electron microscopy [SEM] for descriptive analysis. After application of DBS over dentin substrate and before curing, in the L groups the irradiation was performed over the primer on MP and CSE and after primer/adhesive on SB and SU. After 7 days, the specimens were cut to obtain squared-shape blocks for WS/WSB, slices for one-year DC/MEV and sticks for one-year MS. The data was analyzed by two-way ANOVA, followed by Tukey test for multiple comparisons (p